ATION IN LIBYA SOME ASPECTS OF THE STRUCTURE OF TAXATION IN - غباشي, للدكتور محمد السيد (Dirasat in Economics and Business, 1966)
This article points out in its introductory part the princir taxation which have been referred to by the Libyan legislator in Constitution of the Kingdom as well as the various fundamental slations which were in force in the three Provinces, — Tripolitania, C naica and Fezzan — before the abolition of the federal form of Gove ment. It goes on to follow up the evolution of competence in fiscal matters in Libya before and after the proclamation of the Constitutional Unity of the country in 1963. In this respect distinction is made between the customs duties and other taxes which were necessary to meet the expenditure of the federal Government and the income tax and the monopolies which contributed to the revenue of the Provinces Before the Proclamation of the Constitutional Unity in 1963 and according to article 36 of the 1951 Constitution, customs duties and other taxes necessary to meet the expenditure of the central